Development of Contextual-Based Indonesian Language Teaching Materials to Improve the Reading Ability of Grade VIII Junior High School Students - Harahap, Irmaelianna; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study aims to develop contextual-based Indonesian language teaching materials to improve the reading ability of grade VIII students of SMP Negeri 7 Siobon, Mandailing Natal Regency. The background of this study is the low reading ability of students caused by the lack of interesting, contextual teaching materials, and in accordance with student needs and curriculum. This study uses a Research and Development (R&D) approach with a modified Borg and Gall development model. The development process was carried out through the stages of preliminary study, planning, product development, expert validation, limited trials, product revision, and field trials. The trial subjects were 30 grade VIII students, with data collected through validation questionnaires, student response questionnaires, and reading ability test instruments. The teacher's assessment also showed an average score of 4.2–4.5, which was categorized as good to very good. At the field trial stage, the average score of student responses to the teaching materials was 3.8 (good category), covering aspects of content suitability (3.98), language and image readability (3.7), material presentation (3.8), and visual appearance (3.7). In addition, from the results of the effectiveness test, there was an increase in students' reading ability based on the results of the pretest and posttest. Students showed an increase in scores on the indicators of the ability to find explicit and implicit information, and to conclude the contents of the reading. The developed teaching materials present contextual reading texts, reflective activities, evaluations, and exercises that are arranged based on a contextual approach by considering the students' environment and culture. Learning is arranged in stages and encourages students to think critically and actively in understanding the contents of the reading. Thus, the developed teaching materials are proven to be feasible, practical, and effective in improving the reading skills of grade VIII junior high school students